Financial management for business : cracking the hidden code - Bittlestone, Robert, 1952- (Cambridge : Cambridge University Press, 2010)
Financial Management for Business: Cracking the Hidden Code represents a breakthrough approach to business education. Set against the gripping story of Luca Pacioli's research into the 'Hidden Code' of bookkeeping that transformed medieval business and remains at the heart of every modern enterprise, the book presents an innovative step-by-step model that will transform your understanding of financial management. Key concepts such as profit and loss, cash flow and balance sheets are brought to life with Internet-based simulations that show how cash actually flows around the business. The book also helps to explain how decisions such as pricing and advertising affect the bottom line and why financial disasters happen, such as the 2008 international banking crisis. Professionals and students will find the book an invaluable companion to CIMA's new fast-track financial qualification for non-accountants. The book comes with a free trial of the web-based simulation models: visit www.financial-management-for-business.com for further details.
Machine generated contents note: List of figures; Introduction; Acknowledgements; Part I. A Dream of Future Wealth: 1. Income and outcome; 2. Fool's gold; 3. Play the game; 4. The judgement of balance; 5. Return to reality; 6. The cost of success; 7. Profit and cash; 8. Time to take stock; 9. A capital asset; 10. Mind your own business; 11. The taxonomy of fog; 12. The merchant of Florence; Part II. The Hidden Art of Management: 13. The sweet spot; 14. Elastic bands; 15. An offer you can't refuse; 16. The best of both worlds; 17. Financial perestroika on interstate; 18. Loads of money; 19. Checkmate; 20. Acts of God; 21. Acts of men; 22. Hubble, bubble, double-entry trouble; 23. Credit crunch conclusion; 24. 21st-century accounting; Appendix 1. Mathematical anchor; Appendix 2. Getting to grips with cash; Postscript; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Business enterprises -- Finance; Limited liability